A teoria da justiça de John Rawls e as ações afirmativas : reparar as contingências em direção à igualdade - Fortes, Renivaldo Oliveira (2018)
The aim of this research is to examine the main ideas of John Rawls's (1921-2002) political philosophy present in the conceptual framework of the works A Theory of Justice (1971) and Political Liberalism (1993), as well as to verify to what extent the principles can be sufficiently capable of addressing the problem of the political legitimacy of affirmative action as a public conception of social justice. Considering that Rawls has a vision of a just society and a constitutional democracy that gives priority to certain fundamental rights and freedoms, while at the same time extending equality of opportunity among all people and guaranteeing a minimum of social income for all, if: what is the possibility of a political foundation for affirmative action subsumed under the principles of the theory of justice as John Rawls's equity? In this respect, the hypothesis is proposed that the philosophical presuppositions of Rawlsian justice theory can endorse and legitimize, through the principles of justice as equity, affirmative action policy, which will enable the development of a more just and democratic, with full equality among all citizens. We will also analyze possible answers from contemporary liberal theorists regarding the justification of affirmative action. It seeks to establish contact with some of the authors who dialogued with John Rawls and who addressed the problem of the political and moral legitimacy of affirmative actions. Special mention should be made of some of his main interlocutors in the field of political philosophy, such as Thomas Nagel, Michael Sandel, Amartya Sen and Martha Nussbaum.